Using Stakeholder Cognitive Maps to Inform the Implementation of IRRI’s HER+ West Bengal Livestock Learning Lab - Goswami, R.; Singh, K.; Mukhopadhyay, P.; Chadha, D.; Puskur, Ranjitha; Gartaula, H.N. (2025)
The CGIAR Initiative on Gender Equality addresses four key areas of gender inequality: access to resources, women’s agency, social norms, and policies and governance. In India, its Work Package 2- EMPOWER (Bundled Innovations for Women’s Empowerment and Resilience), led by the International Rice Research Institute (IRRI), focuses on developing and testing context-specific socio-technical innovation bundles (STIBs) to enhance the adoption and benefits of climate-smart agricultural technologies for women. A Theory of Change (ToC) was developed together with partners and key stakeholders to guide the implementation of co-designed STIBs in learning labs (LLs) in West Bengal, India. Learning labs are multisectoral, multistakeholder, and multidisciplinary engagement and learning spaces for collaborative practice and research. The ToC outlined action pathways and preconditions necessary to strengthen climate-resilient livestock management to increase animal productivity in the long term, manifest women farmers’ agencies, and promote viable women-managed enterprises. The envisioned impacts include enhanced empowerment, climate resilience, income, and food and nutritional security of women farmers. However, given the dynamic nature of project implementation and varying socio-economic and environmental conditions experienced by communities, the ToC often needs to be altered to reflect evolving contexts. These adjustments are informed by continuous monitoring and review activities that rely on feedback from past events and are frequently intuitive and ad-hoc. It isn’t easy to adjust the ToC precisely, especially in the initial phase of a project that aims for long-term project outcomes. In complex and intricately interlinked ToCs, intuitive human judgment can suggest changes to project activities but cannot accurately predict the outcomes of revised ToCs. This research report aims to map the achievements and ripple effects of the STIBs implemented through the livestock learning labs by examining how well the project’s progress is aligned with the proposed ToC as perceived by diverse stakeholder groups, taking the project’s ToC as a reference framework. It also analyzes the elements critical to project success within the current context and suggests potential corrective measures to ensure that long-term outcomes are achieved. The findings will highlight the relative effectiveness of different bundles of socio-technical innovations.